2019
DOI: 10.1103/physreva.99.062332
|View full text |Cite
|
Sign up to set email alerts
|

Versatile security analysis of measurement-device-independent quantum key distribution

Abstract: Measurement-device-independent quantum key distribution (MDI-QKD) is the only known QKD scheme that can completely overcome the problem of detection side-channel attacks. Yet, despite its practical importance, there is no standard approach towards proving the security of MDI-QKD. Here, we present a simple numerical method that can efficiently compute almost-tight security bounds for any discretely modulated MDI-QKD protocol. To demonstrate the broad utility of our method, we use it to analyze the security of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 56 publications
0
66
0
Order By: Relevance
“…During the preparation of this paper, we found that Primaatmaja et al 30 proposed an open question that if coding phases in TF-QKD under different bases, which is quite similar to our idea of phase discrete randomization, can improve secret key rate significantly. Their open question is answered by our finding that M = 2 is almost optimal in some sense.…”
Section: Discussionmentioning
confidence: 80%
“…During the preparation of this paper, we found that Primaatmaja et al 30 proposed an open question that if coding phases in TF-QKD under different bases, which is quite similar to our idea of phase discrete randomization, can improve secret key rate significantly. Their open question is answered by our finding that M = 2 is almost optimal in some sense.…”
Section: Discussionmentioning
confidence: 80%
“…The numerical method presented in refs. 10,11 has been shown to be compatible with decoy states-obviating the use of squashing maps-by breaking the infinite-dimensional problem into the dimensions of the signals. This warrants a further study that combines this method with our approach of handling the finite-size statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have ε 0 ¼ ε sec =11 for the calculation with von Neumann entropy (Eq. (11) with SDPs (35) and (36)) and ε 0 ¼ ε sec =10 for the calculation with min-entropy (Eq. (14) with SDP (45)).…”
Section: Basismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, inspired by the work of Ref. [24], we use semidefinite programming (SDP) techniques to estimate the phase-error rate. We note that, in Ref.…”
Section: Introductionmentioning
confidence: 99%